Clinical impact of paravalvular leaks on biomarkers and survival after transcatheter aortic valve implantation. Issue 3 (31st December 2013) - Schewel, Dimitry; Frerker, Christian; Schewel, Jury; Wohlmuth, Peter; Meincke, Felix; Thielsen, Thomas; Kreidel, Felix; Kuck, Karl‐Heinz; Schäfer, Ulrich
<x xml:space="preserve">Abstract</x> Background There is accumulating evidence that up to 20% of the implanted devices after TAVI are associated with a significant degree of paravalvular leaks, which appear to be associated with a negative clinical outcome. Methods A total of 355 patients with severe aortic valvular stenosis (AVS) were treated by TAVI (Corevalve n = 222, Edwards Sapien n = 133). Survival, NT‐proBNP and the grade of PVL were quantified up to 12 months after implantation. Results Technical success rate was 97.8%. Thirty‐day mortality was 9.6%. Post‐procedural transvalvular aortic regurgitation was seen only in a minority of cases (5%), whereas PVL were frequently observed (grade: <1+ in 58.2%, ≥1–<2 in 33.9%, and ≥2 in 7.9%). There was a clear relation‐ship between PVL and adverse outcome (P < 0.001). After a transient increase, NT‐proBNP showed a significant decline. Interestingly, a PVL ≥2+ was associated with a much higher rise in NT‐proBNP compared to the other groups (P < 0.01), and a post‐procedural increase in NT‐proBNP by more than 1640 ng L−1 within 5 days was associated with a significant increase in rate of death (P < 0.01). Conclusions TAVI is an efficient treatment option for high‐risk patients with severe AVS. The incidence of PVL is an inacceptable clinical problem. Serial measurement of NT‐proBNP can be used for risk‐stratification in patients with a significant PVL. In general, PVL graded ≥2+ is associated with a dramatically increased 6‐month mortality. Therefore, any action to reduce paraprosthetical regurgitation is highly recommended. © 2013 Wiley Periodicals, Inc.